Socio-demographic correlation with overweight and obesity among children of North India - Ain Arifa, Quratul; Nabi, Tauseef; Rafiq, Nadeema (Indian Journal of Child Health, 2019)
Background: Nutritional and epidemiological evolution over the past 3 decades has resulted in weight changes. The dramatic rise in childhood obesity is one of its adverse outcomes. Objectives: The aim of the study was to assess the prevalence and socio-demographic correlates of overweight and obesity among school children in the age group of 6–14 years in rural and urban Jammu. Methods: This cross-sectional community-based study was conducted in school going children of both sex aged 6–14 years in rural and urban areas of Jammu region. After explaining the purpose of the study, students were interviewed by the investigator and needful information regarding socio-demographic variables collected. Following the anthropometric assessment, body mass index (BMI) percentiles were obtained from the WHO age and gender-specific BMI charts. Among socio-demographic variables age, gender, residential area, type of school, type of family, education of parents, mother’s occupation, family size, and birth order were analyzed for their relationship with overweight and obesity. Results: Of the 230 children surveyed in the age group of 6–14 years, which included 107 from urban and 123 from rural areas, the overall overweight and obesity observed was 8.2%. Conclusion: Sociodemographic and socioeconomic factors affect the nutritional status of children and adolescents. Overnutrition, as one of its adverse outcome, needs to be addressed with priority so as to prevent the pandemic of obesity and its metabolic consequences.